Tilt and translation motion perception during off-vertical axis rotation - Wood, Scott J.; Reschke, Millard F.; Sarmiento, Laura A.; Clément, Gilles (Experimental brain research, 2007)
The effect of stimulus frequency on tilt and translation motion perception was studied during constant velocity off-vertical axis rotation (OVAR), and compared to the effect of stimulus frequency on eye movements. Fourteen healthy subjects were rotated in darkness about their longitudinal axis 10 degrees and 20 degrees off-vertical at 45 degrees /s (0.125 Hz) and 20 degrees off-vertical at 180 degrees /s (0.5 Hz). Perceived motion was evaluated using verbal reports and a joystick capable of recording tilt and translation in both sagittal and lateral planes. Eye movements were also recorded using videography. At the lower frequency, subjects reported the perception of progressing along the edge of a cone, whereas at the higher frequency they had the sensation of progressing along the edge of an upright cylinder. Tilt perception and ocular torsion significantly increased as the tilt angle increased from 10 degrees to 20 degrees at the lower frequency, and then decreased at the higher frequency. The phase lag of ocular torsion increased as a function of frequency, while the phase lag of tilt perception did not change. Horizontal eye movements were small at the lower frequency and showed a phase lead relative to the linear acceleration stimulus. While the phase lead of horizontal eye movements decreased at 0.5 Hz, the phase of translation perception did not vary with stimulus frequency and was similar to the phase of tilt perception during all conditions. A second data set was obtained in 12 subjects to compare motion perception phase when using a simple push-button to indicate nose-up orientation, continuous setting of pitch tilt alone, or continuous setting of tilt and translation in both pitch and roll planes as in the first data set. This set of measurements indicated that in the frequency range studied subjects tend to lead the stimulus when using a push-button task while lagging the stimulus when using a continuous setting of tilt with a joystick. Both amplitude and phase of tilt perception using the joystick were not different whether concentrating on pitch tilt alone or attempting a more complex reporting of tilt and translation in both sagittal and lateral planes. During dynamic linear stimuli in the absence of canal and visual input, a change in stimulus frequency alone elicits similar changes in the amplitude of both self-motion perception and eye movements. However, in contrast to the eye movements, the phase of both perceived tilt and translation motion is not altered by stimulus frequency over this limited range. These results are consistent with the hypothesis that neural processing to distinguish tilt and translation stimuli differs between eye movements and motion perception.